The skills of the wound navigator in the health care team - Silva, Raquel (2018)
Background: Aging co-morbidities are the main reason for skin changes, requiring qualified professionals to assist the person with this problem [1,2]. In this sense, it emerges in the literature even the tenuous concept – wound navigator, which may enhance the approach to the person with wounds, often described as the tissue viability nurse. Objective: Define the wound navigator and identify his skills. Methods: Integrative literature review using electronic research (CINAHL®, Nursing & Allied Health Collection, Cochrane Plus Collection, MedicLatina, MEDLINE®) and manual research in 12 specialty associations in tissue viability, with the following descriptors (wound OR tissue viability OR ulcer) AND (nurs*) AND (care OR role OR skills OR patient care team OR navigator OR manager OR multidisciplinary OR interdisciplinary OR tissue viability service OR interven* OR pratic*). Inclusion criteria were articles in Portuguese, English, Spanish or French, without temporal limitation, full texts and free access. Exclusion criteria were articles that do not address the study phenomenon. The research was conducted on 08/25/2017, where we obtained 601 articles from the databases and 145 from associations. The titles and abstracts of the publications were read, followed by reading the full text of the selected publications. The sample was defined by 19 articles (15 from databases and 4 from associations). Results: Only one article defines wound navigator, as the health professional with knowledge in the specialty, who acts as a defender of the interests of the clients, which combines the needs felt by them; the objectives of the treatment and the health care treatment plan by referral [3]. It collects the results achieved from the practice and dissemination of research, in order to highlight their actions before the policy of health care [3]. The competences found in the remaining 18 articles were divided into 4 categories: quality (training, auditing, research and elaboration of norms and protocols) management (involvement in product choice, articulation with suppliers, promotion of change and ability to work in multi and interdisciplinary team), care (postgraduate knowledge, experience in the area of tissue viability, prescription of specialized care and treatments with advanced therapies) and leadership (communication, supervision and consulting). Conclusions: There is little literature that precisely defines the wound navigator and his skills, therefore more research is needed to describe in detail. When the term is defined and its competences are known, it may through them formally develop teams with nurses specialized in the area, holders of the general and specific attributes identified.